2017
DOI: 10.1111/jcpp.12812
|View full text |Cite
|
Sign up to set email alerts
|

Practitioner Review: Treatment of chronic insomnia in children and adolescents with neurodevelopmental disabilities

Abstract: Here, we provided a tentative guide for the use of drugs for insomnia in children with NDDs. Well-controlled studies employing both objective polysomnography and subjective sleep measures are needed to determine the efficacy, effectiveness, and safety of the currently prescribed pediatric sleep medicines in children with NDDs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
56
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 71 publications
(60 citation statements)
references
References 121 publications
(138 reference statements)
3
56
0
1
Order By: Relevance
“…The results of Hancock et al on the urinal 6-sulfatoxymelatonin excretion in seven TSCS patients revealed, however, no evidence of abnormal excretion of melatonin in patients with tuberous sclerosis complex and sleep disorder [55,56,83,92]. All but one of the patients showed a normal circadian rhythm of melatonin secretion.…”
Section: Melatonin In Other Neurodevelopmental Disabilities (Ndds)mentioning
confidence: 88%
“…The results of Hancock et al on the urinal 6-sulfatoxymelatonin excretion in seven TSCS patients revealed, however, no evidence of abnormal excretion of melatonin in patients with tuberous sclerosis complex and sleep disorder [55,56,83,92]. All but one of the patients showed a normal circadian rhythm of melatonin secretion.…”
Section: Melatonin In Other Neurodevelopmental Disabilities (Ndds)mentioning
confidence: 88%
“…effect of trazodone is promptly achieved, with possible beneficial effects on sleep architecture and quality in depressed patients. 10 Despite favorable anecdotal reports on the use of trazodone in pediatric insomnia, controlled clinical trials to evaluate its efficacy and safety and appropriate dosages in children are lacking. Currently, there are no clinical data on the pharmacokinetics (PK) or efficacy of trazodone in children, thus presenting challenges for the design of prospective clinical trials to evaluate the efficacy of this drug in children.…”
Section: How Does This Study Add To Our Knowledge?mentioning
confidence: 99%
“…As a result of the combined serotoninergic receptor antagonism and serotonin reuptake inhibition, trazodone has demonstrated unique therapeutic flexibility, which has given rise to its potential use in a broad range of comorbidities of major depressive disorder as well as off‐label indications, including insomnia . Trazodone also shows a sedating activity, with reviews indicating that insomnia is the most common reason for its off‐label prescription and use in adult and pediatric populations . The hypnotic effect of trazodone is promptly achieved, with possible beneficial effects on sleep architecture and quality in depressed patients .…”
mentioning
confidence: 99%
See 2 more Smart Citations